Pengaruh Kualitas Pelayanan dan Lokasi terhadap Minat Pembeli - Titi Hasanah (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of location on purchase intention at Puyang Lahat Coffee Shop, the effect of service quality on purchase intention at Puyang Lahat Coffee Shop, and the effect of location and service quality on purchase intention at Puyang Lahat Coffee Shop. The data analysis method used is quantitative analysis by using validity test, reliability test, classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), hypothesis test (t test and F test) and multiple regression analysis test, and coefficient determination test. . The results showed that location has a significant effect on purchase intention, this can be seen from the value of tcount > ttable (5.229 > 1.986). While service quality has a significant effect on purchase intention, this can be seen from the t count > t table (3.176 <1.986). Also, location and service quality simultaneously have a significant effect on customers, this can be seen from the F count > F table (186, 326 > 3.10) and the significance value < significance level (α) 0.05 (0.000 < 0.05 ). Conclusion, a) the increasing location and quality of service, the increasing interest in buying; b) the increasing the location, the higher the interest in buying; c) the more the location increases, the more interest in buying will also increase. Keywords: Service Quality, Location, Purchase Intention